2008
DOI: 10.1016/j.ejcnurse.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Beta-Blockade in Elderly Heart Failure Patients: Role of the Nurse Specialist

Abstract: Although older age is associated with non-prescription of BB, BB can be implemented in an outpatient HF clinic with nurse specialist support even in elderly patients. although lower doses are achieved than in younger subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
8
0
2
Order By: Relevance
“…The specialist nurses’ main focus should be on patient education and the optimization of medical therapy 26,27. In some European countries, nurses are allowed to prescribe HF drugs, others can up‐titrate prescribed medical therapies, and all should be able to liaise with a hospital or community physician, so that the initiation or optimization of therapy is possible.…”
Section: Specific Points For Setting Up Heart Failure Servicesmentioning
confidence: 99%
“…The specialist nurses’ main focus should be on patient education and the optimization of medical therapy 26,27. In some European countries, nurses are allowed to prescribe HF drugs, others can up‐titrate prescribed medical therapies, and all should be able to liaise with a hospital or community physician, so that the initiation or optimization of therapy is possible.…”
Section: Specific Points For Setting Up Heart Failure Servicesmentioning
confidence: 99%
“…Whilst still not optimal (Komajda et al, 2005) guideline adherence has been found to improve when care is directed by heart failure specialists resulting in reduced inappropriate, omitted or incorrectly dosed medications (Ledwidge et al, 2004) and one way to improve adherence might be the quick up-titration of medicines by specialist nurses before discharge (Ryder et al, 2003). The improved application of guidelines by heart failure specialists has also been demonstrated for beta blockade (Mariani et al, 2008).…”
Section: Influence Of Polypharmacy On Clinician Prescribingmentioning
confidence: 99%
“…Two recent studies on follow-up found that patients declined study participation due to the risk of being assigned follow-up at primary care [ 12 , 33 ]. However, these days, when the competence of primary care has been enhanced with HF nurses and the quality of the care can be ensured [ 34 , 35 ], it would be advantageous and cost-effective to refer stable HF patients who are on optimal dosing of medicines to the primary care, which complies with the guidelines from ESC [ 2 ]. Furthermore, guideline adherence and patient adherence to medication have been found to be maintained when follow-up is managed within primary care [ 12 , 36 ].…”
Section: Discussionmentioning
confidence: 99%